Chemistry for technologists - Palin, G. R. (Commonwealth and international library. Electrical engineering division., 1972)
Chemistry for Technologists provides a basic text on chemical principles written specifically for the technologists. The topics covered are those of basic chemistry. Definitions of such terms as chemical reactions, stoichiometry, and atomic structures are made simple so as not to require prior technical background of the subject.